Meningkatkan Kreativitas Anak Melalui Kegiatan Bermain Warna (Penelitian Tindakan Kelas pada Anak Kelompok B di RA Muslimat NU 107 Khodijah Kramat Duduksampeyan) - Dwi Nurhayati Adhani; Nina Hanifah; Imro’atun Hasanah (Universitas Trunojoyo Madura, 2017)
Children not need social emotional, language, motoric, moral development but alsoneed creativity development. Creativity is ability to produce something new. This study aims to determine creativity development between playing (with coconut pulp). . This research is done by collecting data from various ways that is observation, interview, documentation. The result of this study can be conclude that in RA Muslimat NU 107 Duduk Sampeyan improvement when using playing with coconut pulp. From the results of this study, it can be appealed to early childhood educators to apply byplaying coconut pulp to improve the creativity of children.